THE IMPORTANCE AND PERFORMANCE ANALYSIS OF COMPENSATION PROGRAM IN PT. GRAPARI TELKOMSEL MANADO - Goni, Priskila Hana Debora; Pangemanan, Sifrid S.; Pandowo, Merinda . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Grapari Telkomsel Manado. The research type is quantitative descriptive method, using Importance and Performance Analysis as the analysis tool. 50 employees of PT. Grapari Telkomsel Manado, participated in this research, resulted in  groups of compensation program in accordance to the importance and performance of each compensation program. There were attributes of the compensation program in PT. Grapari Telkomsel Manado:  living allowance, phone credit,  are plotted in quadrant I that indicates a good performance and a high level of importance. Overtime pay are plotted in Quadrant II. The respondents attached a high level of importance to these compensation program, yet have a deficient performance. On the other hand, basic salary are in Quadrant III. They are considered to be not important and have a deficient performance. The company has to pay a special attention to living allowance and phone credit. For an instance, to allocate more resources in order to improve those compensation programs.Keywords: compensation, importance and performance analysis